DESIGN AND PILOT TESTING OF MULTI-MODAL LANGUAGE LEARNING ENVIRONMENTS (MLLEs) FOR EFL STUDENTS: ASSESSING EFFECTIVENESS - Maruf, Nirwanto; Asari, Slamet; Indayani, Wahyu Restu (TELL - US JOURNAL, 2023)
This study aims to assess the effectiveness of Multi-modal Language Learning Environments (MLLEs) in enhancing the language proficiency of English as a Foreign Language (EFL) students. Employing a mixed-methods approach, quantitative analysis of pre-test and post-test scores is combined with qualitative insights drawn from interviews, questionnaires, and observations. Quantitative findings reveal significant improvements across various language skills, including listening, speaking, reading, and writing, with enhancements in mean scores ranging from 10 to 15 points. Decreases in standard deviations suggest increased consistency in post-intervention performance. The t-test results underscore the statistical significance of the enhancements, with highly significant p-values for listening (p < 0.001), significant p-values for speaking (p < 0.01), and marginally significant p-values for reading (p < 0.05). Qualitative thematic analysis sheds light on the immersive and engaging nature of MLLEs, fostering interactive learning experiences and bolstering participants' confidence, motivation, and collaborative skills. However, challenges in reading and writing proficiency underscore the need for tailored content delivery and interventions. The synthesis of quantitative and qualitative findings validates the success of MLLEs in elevating language proficiency. The study's outcomes have substantial implications for educators, curriculum designers, and policymakers aiming to address diverse language learning needs. In conclusion, the study demonstrates the effectiveness of MLLEs in improving EFL students' language proficiency and provides valuable insights for future educational practices. Moving forward, further research can explore additional factors influencing the success of MLLEs.